Prevalence of Pre-diabetes and its associated risk factors: A cross-sectional study in West Tripura district of India - Sengupta, Bitan; Bhattacharjya, Himadri (Indian Journal of Community Health, 2020)
Background: Early detection of Pre-diabetes and controlling the risk factors may delay the development of Diabetes and related complications. Objectives: To estimate the prevalence of Pre-diabetes in West Tripura district of India and to study it’s associations with selected risk factors. Methods: This community based cross-sectional study was conducted in West Tripura district of India, during 1st January 2018 to 31st December 2019 among 320 individuals selected by multistage sampling. Fasting blood sugar was tested for diagnosing Pre-diabetes. Data entry and analysis were performed using SPSS-24. Result: Prevalence of Pre-diabetes in West Tripura district was 19.4%, 28.1% were hypertensive and 32.5% had high BMI. Multivariable logistic regression has identified age ?40 yr (OR: 20.62, 95% CI: 4.97 – 85.49) higher socioeconomic status (OR: 4.99, 95% CI: 1.95 – 12.72), family history of diabetes (OR: 9.72, 95% CI: 2.51 – 37.61), higher BMI (OR: 2.79, 95% CI: 1.32 – 5.89) and physical inactivity (OR: 3.52, 95% CI: 1.66 – 7.46) as the predictors of Pre-diabetes. Conclusion: West Tripura district of India has higher prevalence of pre-diabetes than the national average. Age ?40 yr, higher socioeconomic status, family history of diabetes, higher BMI and physical inactivity were identified as significant predictors of Pre-diabetes in this region.